Experimental Study of the Combined Action of Random Waves and Current Induced Hydrodynamics and Seabed Response Around a Protective Three-Dimensional Pipeline - Dayu Chang; Risheng Wang; Wenqi Si; Mengxiao Li; Zheng Wang; Dajun Liu; Ke Sun; Dong-Sheng Jeng; Lin Cui; Dejian Wei (Journal of Marine Science and Engineering, 2026)
Submarine pipelines serve as the primary transportation infrastructure for offshore energy resources and are becoming increasingly important in modern industrial and domestic applications. A series of laboratory experiments on the dynamic seabed response of three-dimensional pipeline-seabed systems under random wave and current conditions was conducted. The results demonstrate as follows: (1) Under the combined action of random waves and ambient currents, the wave profiles in the vicinity of the submarine pipeline exhibit distinct irregular and nonlinear characteristics; (2) Compared with random waves acting alone, the superposition of random waves and currents modifies wave propagation behavior: a co-directional current enhances wave propagation, whereas a countercurrent suppresses it; (3) For a pipeline subjected to the three-dimensional random waves, pore-pressure amplitude decreases with increasing wave-incidence angle. Specifically, maximum values corresponding to incidence angles of 30° and 45° are generally lower than those at 0° and 15°, at a seabed depth of z/d = 0.0938, and the value at an incident angle of 45 degrees attenuates by 21.31% compared to that of 0°; (4) Coarse sand exhibits weaker pore-pressure attenuation than fine sand around the three-dimensional pipeline-seabed scheme, indicating that sediment grain size exerts a substantial influence on seabed response; (5) The protective effect of geotextile and stone is more obvious, whereas PVC is limited to the front and underside of the pipe. The deeper the seabed, the smaller the effect of protective measures. For reproducibility, the test matrix covered wave-incidence angles α = 0°, 15°, 30°, and 45°, irregular-wave conditions with H1/3 = 0.08–0.14 m and T1/3 = 1.2–1.8 s, and currents U = –0.2 m/s at a constant still-water depth h = 0.45 m.